ANALYSIS OF EMBANKMENT ON GYPSEOUS SOILS - H. Abdul-Kareem, Ahmed (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT:The gypseous soils are distributed in many regions in Iraq and other countries. Therefore, it is necessary to study the behavior of such soils due to the large damages that affects the structures founded and constructed in or on it.This research is concerned with studying the effect of leaching soil process on the stability of an embankment erected on foundation gypseous soil. The finite element method is adopted in this research. The analyses carried out using a nonlinear, increment, and stress-dependent finite element computer program. The hyperbolic stress-strain parameters used in the finite element analyses are estimated by the data collected from triaxial compression tests of some researchers. The analysis of the embankment problem carried out, shows that the leaching process for foundation gypseous soil increases the displacements and deformations of the embankment and its foundation. Finally, this research necessitate the success using of the finite element method in design and analyses of the important structures and buildings erected on gypseous soils that may expose to the effect of leaching process. This means that there is possibility to predicate the behavior of structure by a powerful means to establish the suitable solutions for any problems that may be occurred as a result of the present gypseous soil.